Analisis kondisi perkerasan lentur pada Jalan Margomulyo Kecamatan Asemrowo Kota Surabaya dengan metode Pevement Condition Index (PCI) - Selan, Mikdon Tobi; Tjendani, Hanie Teki (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Margomulyo Street is in Asemrowo District, which is an area in West Surabaya that is famous for its industrial and warehouse complexes. The dense traffic of heavy vehicles such as trailers and other logistics trucks around industrial areas is the main cause of road pavement structures becoming susceptible to damage, including cracks, holes, and deformation. To maintain the pavement structure at the planned service level, a series of actions are called maintenance and repair. Therefore, to evaluate more deeply the condition of the road pavement, the Pavement Condition Index (PCI) method is used. Based on the results of the visual survey, there are several damages and percentage values, namely Weathering and Raveling (46,94%), Rutting (26,35%), Alligator Cracking (11,68%), Corrugation (5,17%), Longitudinal & Transverse Cracking (3,36%), Block Cracking (3,20%), Depression (1,30%), Potholes (1,07%), Patching & Utility Cut Patching (0,66%), Bleeding (0,24%), dan Edge Cracking (0,04%). And based on the results of data analysis, the PCI value on Margomulyo Road is 56.21% (Good).